Sliding bearing with adjustable friction properties. Issue 1 (2016) - Engel, T.; Lechler, A.; Verl, A.
Abstract: Sliding bearings have good damping properties and a high stiffness. However, stiction and poor sliding friction characteristics limit their use in applications, where high requirements are defined on the smoothness of motion. By inducing ultrasonic oscillations into the sliding contact it is possible to actively control the friction. The adjustable friction bearing uses this principle. This leads to a new bearing type that has the stiffness and damping properties of a sliding bearing, while at the same time, offering a linear friction characteristic without stiction. This paper presents basic principles for the design of ultrasonic bearings along with experimental results of a friction-adjustable machine table.